THE PROBLEM OF MOTIVATION AND METHODS OF ITS INCREASE AT STUDENTS OF NOT LANGUAGE TRAINING DIRECTION IN TEACHING FOREIGN LANGUAGE - Olga A. Danilova; Alexander A. Somkin; Vyacheslav M. Meshkov (National Research Mordova State University, 2016)
Introduction: the article is devoted to such an actual today issue as increasing of motivation of students learning foreign languages in non-language faculties of a contemporary university. The authors identify the main reasons causing the low level of language preparation among students of non-linguistic directions of preparation, which include - lack of motivation for the implementation of utterance (dominated by a strong belief that in real life it is not useful); small vocabulary; poor knowledge (or ignorance) of grammar of the language being studied; the fear of making a mistake ("psycholo gical barrier"). Materials and Methods: the methodological basis of the research are scientific methods such as observation and experiment. In addition, the authors used some other methods such as study of students' performance (written, examinations, tests, essays, dictations, summaries, etc.); method of pedagogical experiment; modeling. Results: in order to change this situation, the authors suggest to activate the teaching and speech activity of students at two levels: 1) motivation and impelling (to form among students sustained motive (need) to speak) and 2) tentatively and research (to train the ability to independently select and apply language and speech means appropriated to conditions and social environment). One must skillfully combine both traditional and innovative approaches and methods in the teaching of foreign languages, among which the authors identify a number of basic: the so-called gambling technology (business and role-playing games), information and communication technologies (presentations, projects, online tutorials, webinars), Internet communication with foreign counterparts, meetings and discussions with native speakers, participate in competitions and others. Their alternation on pairs will maintain the attention and interest of students at a high level. Discussion and Conclusions: it is noted that a key role in this process is given the personality of a teacher who should possess such qualities as professionalism, language competence, creative thinking, the ability to model the learning process and adapt it in accordance with the level of preparedness of specific audiences, etc.